Prestige auditing and the market for academic esteem: a framework and an appeal. (1st March 2017) - Elliott, J. E.
Abstract : Much has been written about the remarkable rise of global university rankings from their initial appearance in the Academic Ranking of World Universities (Shanghai) tables in 2003. The examination of all things rankings, however, has arguably outpaced its conceptual uptake. This paper addresses this imbalance by reviewing prestige audits as resource management tools and status allocation measures. The paper argues that audit ambition has courted audit failure in both dimensions. The resource management justification underestimates the challenge of devising reliable proxy variables across international higher education sectors, organizational types, and disciplinary/departmental objectives. Evidential data sets are duly recast as data narratives that compete with each other and cloud the ordinal clarity aspired to in ranking tables. The status competition approach generates Matthew effects and encourages factor gaming. Positional goods investments are also socially and economically wasteful. In either strict (rigid) or relaxed (normed) form, finally, their zero-sum logic fails to account for private and public externalities. The paper closes with an appeal to soft-variable evaluations in higher education contexts as well as to closer scrutiny of the vocabulary informing both quantitative and qualitative assessments.